PKM sosialisasi pengukuran tingkat kesegaran jasmani murid Sekolah Dasar Nomor 84 Kabupaten Sinjai - Andi Ihsan; Hasbi Asyhar (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Symptoms of physical fitness among children in areas is a common symptom where the main cause is they are lessmobile, caused by the lack of time to do physical activities. Children are so engrossed in playing in front of computers, laptopsand cellphones, eating unhealthy foods are instantaneously triggering the emergence of various diseases that at times threatentheir health. Measurement of the level of physical fitness is one of the parameters to determine the level of physical fitness of aperson. The level of physical fitness is a person's fitness level in carrying out daily activities. Physical fitness is the physicalcondition of a person related to the ability and ability to carry out work activities optimally and efficiently. Physical fitness ofelementary school students is different from physical fitness for functional junior high school and senior high school student,because physical fitness is individual. Thus the measurement of physical fitness level for someone is very important to know thephysical education teachers in elementary schools. The socialization of physical fitness measurement to physical educationteachers and elementary school students number 84 in Sinjai Regency uses a physical fitness test prepared by the Center forPhysical Fitness and Recreation called TKJI (Indonesian Physical Fitness Test, specifically for elementary school age 10-12years). This test uses 5 (five) test items which must be carried out in the overall order, namely: (1) 40 meter running (2) bendingelbow hanging (3) lying down sitting 30 seconds (4) jumping upright and (5) running 600 meters. The location of this scienceand technology application was carried out in the elementary school football field number 84 of Sinjai Regency with the target ofall physical education teachers and elementary school students numbering 71 people. The results achieved are physical educationteachers realize the importance of understanding and mastery of physical fitness level tests of elementary school students aged10-12 years in the teaching and learning process especially in improving the health status of students in SD No. 84 SinjaiRegency. The physical awareness level testing activity can overcome the limitations of the TKJI test implementation guidelineswell. By carrying out the socialization of physical fitness level test, it can foster an attitude of love for exercising to students,especially the introduction and understanding of individual physical fitness level test items. It is expected that elementary schoolphysical education teachers to always carry out tests of physical fitness level to students or students to the fullest, of course, withnationally standardized test items with the implementation process in the right order.